Functionalized Microgel Rods Interlinked into Soft Macroporous Structures for 3D Cell Culture (Adv. Sci. 10/2022). Issue 10 (5th April 2022) - Rommel, Dirk; Mork, Matthias; Vedaraman, Sitara; Bastard, Céline; Guerzoni, Luis P. B.; Kittel, Yonca; Vinokur, Rostislav; Born, Nikolai; Haraszti, Tamás; De Laporte, Laura
Abstract : Rod‐Shaped Microgels A two‐component system consisting of microgel rods creates macroporous interlinked constructs for cell culture in 3D with pores up to several hundreds of micrometers. The functionalized microgel rods that interlink with each other in aqueous solutions without further additives are produced via microfluidics in a continuous plug‐flow on‐chip gelation method. More details can be found in article number 2103554 by Laura De Laporte and co‐workers.